2021
DOI: 10.25271/sjuoz.2021.9.3.829
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Protein Source and Its Levels on Egg Production and Egg Quality of Japanese Quail (Coturnix coturnix japonica)

Abstract: Fish and soybean meal are known as common utilized crude protein sources in poultry diets. Quail birds often need higher requirements of dietary protein which influences its productive performance. The aim of the experiment is to determine the impact of protein source with different levels on egg production and egg quality characteristics. The experiment was carried out at animal production dept., University of Duhok, Kurdistan Region- Iraq, during spring 2020 for 56 days. The birds were divided into two main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“… Jesuyon et al (2021) discovered additional evidence that the weight of laying quail eggs increased due to the crude protein concentration of diets. On the other study, Salih et al (2021) reported in a different study that greater crude protein diet contents led to better egg production, egg mass, and feed conversion ratio. According to Macelline et al (2021) and Mnisi et al (2022) , the protein supply from meals is crucial for the synthesis of eggs, and increased crude protein concentrations may improve the egg production of laying quails.…”
Section: Discussionmentioning
confidence: 94%
“… Jesuyon et al (2021) discovered additional evidence that the weight of laying quail eggs increased due to the crude protein concentration of diets. On the other study, Salih et al (2021) reported in a different study that greater crude protein diet contents led to better egg production, egg mass, and feed conversion ratio. According to Macelline et al (2021) and Mnisi et al (2022) , the protein supply from meals is crucial for the synthesis of eggs, and increased crude protein concentrations may improve the egg production of laying quails.…”
Section: Discussionmentioning
confidence: 94%